Grape Leaffolder, Desmia funeralis (Hübner) (Insecta: Lepidoptera: Crambidae) - F. W. Mead; Susan E. Webb; Oscar E. Liburd; Elena M. Rhodes (EDIS, 2022)
The grape leaffolder is a common and widely distributed species that is a minor pest of grapes in the United States. In California severe outbreaks have occurred in restricted areas during some years. These outbreaks have been associated with failures of parasites to attain their normal levels. In Florida the grape leaffolder has done substantial damage to grape leaves in September and October when growers have discontinued their spray programs after harvest. Excessive defoliation may deplete the food reserves in the vine sufficiently to reduce the size of the next crop.